(untitled) (Revista de Estudos da Linguagem, 2024)
Widely known in Brazil, cordel leaflets are active in the Northeastwhich characterizes a group memory. For this reason, this article emphasizes the idea that this textual genre is manifested and propagated by the historical-discursive bias, supported by an oral tradition and based on an outlined prototypical model. According to Rodrigues (2011), text is the product of human interaction (communication and socialization) and extrapolates purely verbal aspects, involving external elements, which are consistent with the contextual and cultural universe, proper to the socio-historical practice that is language. Based on exploratory, descriptive and bibliographic research, the study investigates phenomena of tradition, permanence and change present in the covers of cordel leaflets. Therefore, from a symbolic-anthropological bias (DURAND, 2002) of the sciences of meanings, the study dialogues with the theoretical assumptions of Discursive Traditions (TD), disseminated by Kabatek (2006, 2012) and Coseriu (1980); in addition to cultural studies and oral tradition (ZUMTHOR, 1993), cordel pamphlets and Anthropological Semiotics (RODRIGUES, 2011, 2014a, 2014b, 2017, 2018a, 2018b). Through the analyzes carried out, he concludes that the cordel leaflets are instruments of representation and maintenance of the Northeastern popular memory, revealing on their covers portraits of the region, its culture, memory and imagery. In addition to its structure (architecture and support), the cord opens multiple possibilities for study and understanding of its performance/updating as a social practice in northeastern culture through reading and verb-visual/multimodal composition, which allows its continuity and maintenance the voices of the culture it represents.